Pengaruh Value Terhadap Organisasi Dan Kebersaingan - Dito Pramu Dita (CV. RO BEMA, 2024)
This article discusses the role of values in influencing organizational success and business competitiveness. In today's digital era, technology can also be used to increase the value provided to customers. Organizations can utilize technology to provide faster and more efficient services, as well as make it easier for customers to make transactions. By prioritizing value in the organization and competitiveness, it is hoped that it can help organizations to remain relevant and develop in an increasingly competitive market. Organizations that are able to provide good value and consistently to customers will be better able to survive and thrive in market competition. To achieve this, organizations must have a good understanding of customer needs and wants and the ability to provide quality products or services at competitive prices. In addition, the organization also needs to be able to differentiate the value generated from its competitors. In this case, the organization must be able to understand the uniqueness of its product or service, and offer advantages that are not owned by its competitors. This can make the organization stand out in the marketplace and earn greater profits.